Analyses of Geospatial Variability Effect on Food Security Status of Cassava Producers in Nigeria, and its Determinants (British Journal of Multidisciplinary and Advanced Studies, 2023)
Production, and consumption of Agricultural crops remains an important tool in cushioning the random effect of food insecurity, poverty and unemployment in households as these are prevalent in both urban and rural Nigerian households. In this regard, data collected by National Bureau of statistics on General Household Survey (GHS, wave 3) was used to profile the food security status in four Geopolitical Zones as they were representative of large samples for the study that comprised 1000 cassava - based farming households, while descriptive statistics, Foster, Greer, and Thorbecke (FGT), and logistic regression were utilised as analytical tools. The result shows that food insecurity incidence of the study area was 0.41 and although relatively higher (59%) of the households were food secure, a fair high proportion (41%) were food insecure in the study area. However, geospatial variation analyses across the zones showed that food insecurity incidence was at 0.66, 0.44, 0.43 and 0.34 for North-Central, South-West, South-South and South - East respectively, while it is canonically highest in the rural areas, relative to the urban areas, while Gender, age, years of schooling, crop consumed from own production, household size, marital status, per capita non-food expenditure, cost of meal taken away from home and regional, and locational factors are significant determinants of food security among the cassava-based farming households across the geopolitical zones in Nigeria. The study concluded that socioeconomic and geospatial variability significantly influence food security among cassava-based farming households in Nigeria, and further recommended useful policy options.